1991
DOI: 10.1111/j.1469-8137.1991.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in acidic pollutant inputs and their effects on the chemistry of stemflow, bark and epiphyte tissues in three oak* woodlands in N.W. Britain

Abstract: SUMMARYRainfall, throughfall and stemflow chemistry, bark chemistry and gaseous air pollutant levels were monitored for one year within three Quercus petraea (Mattuschka) Liebl. woodlands in north west Britain. Tissue chemistry of the epiphytic lichen Lobaria pulmonaria (L.) Hoffm, and the moss hothecium myosuroides Brid. were also studied at the sites in which they were abundant. The sites were found to difFer in the levels of acidic and nutrient inputs, bark chemistry and levels of gaseous pollutants, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 36 publications
(19 reference statements)
2
55
0
Order By: Relevance
“…Cadle et al (1991) found for a range of species fumigated with nitric acid vapour, that stem and branches adsorbed 5-10 times more than the leaves when calculated on an area basis. Several workers have also shown that twigs and bark enrich throughfall to a greater extent than leaves (Schulze, 1989;Farmer et al, 1991). Van Breeman et al (1982) found that stemflow was enriched with ammonium to a greater extent than throughfall in an oak/birch woodland.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Cadle et al (1991) found for a range of species fumigated with nitric acid vapour, that stem and branches adsorbed 5-10 times more than the leaves when calculated on an area basis. Several workers have also shown that twigs and bark enrich throughfall to a greater extent than leaves (Schulze, 1989;Farmer et al, 1991). Van Breeman et al (1982) found that stemflow was enriched with ammonium to a greater extent than throughfall in an oak/birch woodland.…”
mentioning
confidence: 98%
“…Potter et al (1991) found that nitrification of ammonia by leaf surface microflora played no role in nitrogen transformation in an American hardwood forest. Epiphytic macroflora can, however, impose problems for interpretation of stemflow nutrient changes (Farmer et al, 1991). Work on beech showed that algae probably played a significant role in nitrogen losses, judging from a '''N budget analysis.…”
mentioning
confidence: 99%
“…Most workers have tended to concentrate on species growing in grassland, for example Hylocomium splendens and Pleurozium schreberi (Ross, 1990), or on Sphagnum species from ombrotrophic mires (Press et al, 1986 ;Pitcairn et al, 1995). Epiphytic mosses, usually those on tree trunks, have also been used, for example Hypnum cupressiforme (Goodman & Roberts, 1971) and Isothecium myosuroides (Farmer et al, 1991). However, these groups of species are often absent from the urban environment, or are of limited value for this kind of work in towns and cities where a good deal of the pollution from traffic occurs (Goodman & Roberts, 1971 ;Ross, 1990 ;Tyler, 1990).…”
Section: mentioning
confidence: 99%
“…In contrast to the element content of soil, there is no standard method for determining the availability of cations from bark. While in numerous studies, including HAUCK (2000) and HAUCK et al (2001b), the element content of bark is specified as the total content, extracts with SrCl 2 or BaCl 2 were used for cation measurements by FARMER et al (1991) and GOWARD & ARSENAULT (2000). However, these extractants are perhaps not appropiate for assessing the exchangeability of heavy metals from organic surfaces (BRANQUINHO et al 1997) physodes soredia, even before they start to grow.…”
Section: Discussionmentioning
confidence: 99%
“…In low-polluted areas, cation uptake and resulting physiological effects have been scarcely studied in lichens (HAUCK 2003), cation sources for lichens are the substrate, precipitation and particles from dry deposition (FARMER et al 1991, HAUCK 2000. ULOTH (1861) showed that the foliose lichens Evernia prunastri had higher concentration of Fe on sandstone than on birch bark.…”
Section: Element Contents Of Lichensmentioning
confidence: 99%